Compact passive Q-switching of a diode-pumped Tm, Y:CaF2 laser near 2 μm. (July 2018) - Zhang, Cheng; Liu, Jie; Fan, Xiuwei; Peng, Qianqian; Guo, Xinsheng; Jiang, Dapeng; Qian, Xiaobo; Su, Liangbi
Highlights: The continuous wave characteristics of Tm, Y:CaF2 laser were researched. The highest continuous wave slope efficiency of 51.5% is firstly obtained. Passively Q-switched Tm, Y:CaF2 laser at 2 μm is demonstrated for the first time. Graphene oxide is used as saturable absorber in passive Q-switching operation. Abstract: Lasing was realized near a wavelength of 2 μm with a compact linear cavity by using a fiber-coupled 792-nm laser diode as the pump source and a Tm 3+, Y 3+ co-doped CaF2 crystal. By employing broadband graphene oxide (GO) as the saturable absorber (SA), a passive Q-switching Tm, Y:CaF2 laser was implemented for the first time. When the transmission of the output couple (OC) was 2%, the maximum average output power was measured to be 400 mW with a corresponding repetition rate of 20.22 kHz and a pulse width of 1.316 μs. A maximum continuous-wave (CW) output power of more than one watt was obtained with slope efficiency of 51.5%.